The Effect of Innovation Culture and Job Satisfaction on Relation between Human Resources Management and Employees’ Ownership in Shahr Bank of Tabriz - Iranzadeh, Soleiman (International Review of Management and Marketing, 2017)
The aim of this study is to investigate the effect of innovation culture (IC) and job satisfaction (JS) on the relation between human resource management (HRM) and employees’ ownership (EO) in Shahr Bank of Tabriz. This research is applicable in terms of aim, descriptive and correlated in terms of data gathering and quantitative (i.e., using a questionnaire) in terms of the type of data gathering. Statistical population of this study is Shahr Bank employees in Tabriz. Considering the fact that there are 100 employees working in seven branch offices and 11 office counters of Shahr Bank around Tabriz, the research questionnaires were distributed over the whole population. Visual-PLS software was used to analyze data provided by the questionnaires through structural equation modeling. Results from findings in this research show that the strategic HRM, IC and JS have a positive effect on the EO. Moreover, IC increases the JS among employees. Keywords: Innovation Culture, Job Satisfaction, Strategic Human Resource Management, Employee Ownership JEL Classifications: E37, E32, C53, C5